Fenofibrate Ameliorated Systemic and Retinal Inflammation and Modulated Gut Microbiota in High-Fat Diet-Induced Mice - Wang, Xue; Yu, Chaofeng; Liu, Xiaomei; Yang, Jiasong; Feng, Yuliang; Wu, Yajun; Xu, Yali; Zhu, Yihua; Li, Wensheng (Frontiers in Cellular and Infection Microbiology, 2022)
Fenofibrate, as a lipid-lowering drug, has been reported to have a protective effect on the retina independent with plasma lipid levels. This study aimed to investigate that the ameliorative effects of fenofibrate on systemic and retinal inflammation, as well as gut microbiota dysbiosis in high-fat diet (HFD)-induced mice. C57BL/6J mice were randomly allocated into four groups: standard diet (SD) group; HFD group; SD plus fenofibrate (SD_ Fe) group; HFD plus fenofibrate (HFD_ Fe) group. After successfully establishing models (5 months), indicators associated with lipid, gut barrier, inflammation and gut microbiota were investigated. Our results showed that supplementing the HFD with fenofibrate decreased body weight gain, alleviated dyslipidemia and reversed the downregulation of short-chain fatty acid (SCFAs) in serum, retina and feces. Fenofibrate ameliorated intestinal barrier function damage in HFD-induced mice. Fenofibrate coadministration inhibited the levels of inflammatory factor and lipopolysaccharide (LPS) in the serum and attenuated inflammatory response in the retina of HFD-induced mice. Systemic LPS was positively correlated with a series of inflammatory factors in serum and retina, respectively. Fenofibrate supplementation down-regulated the abundances of LPS-associated bacteria in HFD mice, including Firmicutes and Proteobacteria at the phylum level, Desulfovibrionaceae at the family level, as well as unclassified_ Desulfovibrionaceae, Acetatifactor, Flavonifractor, Oscillibacter and Anaerotruncus at the genus level. However, fenofibrate treatment up-regulated the abundances of SCFA-associated bacteria in HFD mice, including Bacteroidetes at the phylum level, Porphyromonadaceae at the family level, as well as unclassified_Porphyromonadaceae, Barnesiella, Alloprevotella and Bifidobacterium at the genus level. In conclusion, our results confirmed fenofibrate could attenuate HFD-induced systemic and retinal inflammation, accompanying with restoration of intestinal barrier damage and modulation of gut microbiota/metabolites. This work provided an explanation for the ameliorative effects of fenofibrate on HFD-induced systemic and retinal inflammation might be partially related with the modulation of gut microbiota and its metabolites.